2009
DOI: 10.1152/ajpgi.00108.2009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of stretch-activated excitatory and inhibitory responses in the lower esophageal sphincter

Abstract: We recently found that an orally directed stretch of the esophagus activates a neurally mediated relaxation of the lower esophageal sphincter (LES). Goals of our study were to characterize the neural mechanisms responsible for axial and transverse stretch-activated responses in the LES. LES pressure was monitored in anesthetized and artificially ventilated mice. Sutures were placed in the esophagus to exert graded stretch in the longitudinal and transverse directions. Effects of bilateral vagotomy and pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
45
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 38 publications
10
45
0
3
Order By: Relevance
“…Furthermore, stretch-activated reflexes exist in the stomach, where there are no IPANs (41). Our earlier in vivo studies (7,22,23) and the present in vitro study clearly prove that the inhibitory motor neurons are indeed mechanosensitive. Our findings are in agreement with the concept of multifunctionality of myenteric neurons proposed by Schemann and colleagues (28,29), who demonstrated that a large number of myenteric neurons possess sensory, integrative, and motor functions in the same cell.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Furthermore, stretch-activated reflexes exist in the stomach, where there are no IPANs (41). Our earlier in vivo studies (7,22,23) and the present in vitro study clearly prove that the inhibitory motor neurons are indeed mechanosensitive. Our findings are in agreement with the concept of multifunctionality of myenteric neurons proposed by Schemann and colleagues (28,29), who demonstrated that a large number of myenteric neurons possess sensory, integrative, and motor functions in the same cell.…”
Section: Discussionsupporting
confidence: 80%
“…In whole animal studies, we found that mechanical stretch of the esophagus in the axial and transverse directions induces neurally mediated LES relaxation and LES contraction, respectively (22,23). Pharmacological analysis of in vivo studies suggests that esophageal motor neurons might be mechanosensitive (22); however, this novel notion needs direct evidence. Moreover, although a growing body of literature suggests that enteric neurons respond directly to mechanical stretch in the small intestine and colon (6,28,36,41), whether isolated enteric neurons are mechanosensitive has not been studied.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Assuming that the extent of yield amounts to ϳ50% elongation, the size of the stretched and effaced LES closely corresponds to the observed 4-cm length of the ampulla at the time of the CDP. These observations also fit well with the recent demonstration that axial traction on the LES activates neural pathways that elicit LES relaxation, possibly mediated by mechanosensitive enteric neurons in the LES segment (8,9). Concurrent with this axial traction, the distal esophagus is tethered to the CD by the phrenoesophageal ligament.…”
Section: Discussionsupporting
confidence: 89%
“…Axial stretch of esophagus in the oral direction activates neurologically mediated LES relaxation and possibly descending relaxation of the esophagus (7). Therefore, it is hypothesized that longitudinal muscle contraction related axial stretch is of fundamental importance in the descending relaxation of the peristaltic reflex.…”
mentioning
confidence: 99%